THE OPPORTUNITIES AND CHALLENGES HALAL TOURISM IN BANDUNG-INDONESIA REGENCY - Parhan, Muhamad; Rindu Fajar Islamy, Mohammad; Budiyanti, Nurti; Hari Nugraha, Risris; Eka Subakti, Ganjar; Fuaddin, Ahmad (Jurnal IPTA (Industri Perjalanan Wisata); Vol 9 No 1 (2021): Jurnal IPTA (July 2021)DO - 10.24843/IPTA.2021.v09.i01.p08, 2021)
A new phenomenon that is developing in the world of tourism is halal tourism. Halal tourism is tourism which in its implementation refers to the Islamic law, both in terms of accommodation, attractions, facilities, services and the tourist attractions it self. In Bandung regency, halal tourism is not well known and is still in the preparation stage of development, so that attention and concern for halal tourism in this regency has not yet been developed. Bandung regency Government is in the process of making policies related to the concept of halal tourism. The purpose of this study is to analyze the opportunities and challenges of halal tourism development in Bandung regency and its impact on tourist arrivals to Bandung regency. The research method used in this research is descriptive analysis method. Research data were collected using interview techniques, observation of events in the community and literature studies. The results of this study illustrate that Bandung Regency has a great opportunity in applying the concept of halal tourism because the majority of residents and tourists are Muslim, while the challenges need to be synergized with the policies of a leader, manager and various elements of the community to support Islamic accommodation, attractions, facilities and services .